Using data envelopment analysis for estimating energy saving and undesirable output abatement: a case study in the Organization for Economic Co-Operation and Development (OECD) countries - Rashidi, Kamran; Shabani, Amir; Farzipoor Saen, Reza (Journal of cleaner production, 2015)
Environmental protection is one of the main concerns of the international community. Countries show meticulous attention to environmental issues by considering eco-efficiency. The eco-efficiency evaluation of countries is a complex and multidisciplinary topic. Data envelopment analysis has widely been applied to measure the eco-efficiency of organization for economic co-operation and development countries. In previous studies, energy inputs have not been contemplated. The subject becomes more important when there are non-discretionary factors. In this paper, the eco-efficiency of countries in the organization for economic co-operation and development is assessed given energy inputs, undesirable outputs, and non-discretionary factors. To this end, slack-based and range-adjusted measures are extended. Also, new environmental indices are introduced. The relationship between consumption of energy inputs and production of undesirable outputs can be addressed by two new environmental indices. Spearman correlation test indicates a direct and positive relationship between potential of energy saving and potential of undesirable output abatement. France, Germany, Luxemburg, Norway, Sweden, and the United Kingdom are recognized as eco-efficient countries. South Korea and Italy have the highest and lowest potential for energy saving, respectively. Poland and Iceland are countries with the highest and lowest potential for undesirable output abatement, respectively. It can be concluded that countries producing high undesirable outputs may not operate eco-efficiently and thus have an extreme potential to save the optimum energy. Moreover, countries consuming low energy may operate eco-efficiently and have a low potential to reduce undesirable outputs. •We develop two DEA models to evaluate performance of the OECD countries.•The proposed models take into account energy inputs and undesirable outputs.•Two new environmental indices are given.